Anxiety, Depression and Stress of university students due to the resumption of classes in pandemic time - da Fonseca, Amândio Jamba Pedro (2021)
The COVID-19 pandemic is a threat to human health, it is identified as a significant stressor that puts at risk the psychological health and well-being of people around the world; it can trigger mild and severe levels of psychosocial problems. The objective of this study was to describe the levels of anxiety, depression and stress of Higher Polytechnic Institute of Bié students in the municipality of Kuito in Angola. This is a quantitative, non-experimental, cross-sectional study with a descriptive scope. With the non-probabilistic accidental criterion, 376 students participated from the Social Communication, Accounting and Administration, Computer Engineering and Psychology courses, participated 140 women (37.23%) and 236 men (62.77%), aged 18 to 60 years, with an average age of 25.99 years. The data collection was from October 5 to 30, 2020 and the analysis was during the months of January and February 2021. The Anxiety, Depression and Stress Scale, EADS-21 was applied (Pais-Ribeiro, et al., 2004), it is a scale composed by three sub-scales distributed in 21 items that evaluate: Anxiety, Depression and Stress, evaluated through a type response scale Likert, 4 points. The results show that students have low levels of Anxiety, Depression and Stress. It is concluded that, in females, aged between 18 and 30 years, in the first years of courses and in Accounting and Administration and Psychology courses, there are greater effects on the Anxiety, Depression and Stress indicators.